A comparison of functional outcome between amputation and extension prosthesis in the treatment of congenital absence of the fibula with severe limb deformity. (August 2017) - Calder, P.; Shaw, S.; Roberts, A.; Tennant, S.; Sedki, I.; Hanspal, R.; Eastwood, D.
Purpose: Complete fibula absence often presents with significant lower-limb deformity. Parental counselling regarding management is paramount in achieving the optimum functional outcome. Amputation offers a single surgical event with minimal complications. This study compares outcomes with an amputation protocol to those using an extension prosthesis. Method: Thirty-two patients were identified. Nine patients (2 males, 7 females; median age at assessment of 23.5 years) used an extension prosthesis. Twenty-three patients (16 males, 7 females; median age at assessment of eight years) underwent 25 amputations during childhood. Mobility was assessed using SIGAM and K scores. Quality of life was assessed using the PedsQL inventory questionnaire; pain by a verbal severity score. Results: The 19 Syme and one Boyd amputation in 19 patients were performed early (mean age 15 months). Four Syme and one trans-tibial amputation in four patients took place in older children (mean age 6.6 years). Only two underwent tibial kyphus correction to aid prosthetic fitting. K scores were significantly higher (mean 4 vs 2) and pain scores lower in the amputation group allowing high impact activity compared with community ambulation with an extension prosthesis. The SIGAM and PedsQL scores were all better in the amputation group, but not significantly so. Conclusion: Childhood amputation for severe limb length inequality and foot deformity in congenital fibula absence offers excellent short-term functional outcome with prosthetic support. The tibial kyphus does not need routine correction and facilitates prosthetic suspension. Accommodative extension prostheses offer reasonable long-term function but outcome scores are lower.